Annual Plan 1990-91 Punjab - Planning Commission (Planning Commission, 1990)
The Seventh Plan size for the Punjab State had been fixed at Rs. 3285.00 crores. the expenditure during the first four years of the Seventh Plan has, been Rs. 2677.14 crores. An outlay of Rs. 789.00 crores, including Rs. 89.00 crores exclusively earmarked for Police, has been provided for the year 1989-90. An allocation of Rs. 905.00 crores has been approved for the Annual Plan 1990-91.
Planning Department, Punjab